Mechanical properties of ECC connection plates in seamless Bridges - Ziwang Xiao; Lifeng Wang; Rikang Huang (PLoS ONE, 2026)
Seamless bridges require high-performance connection systems due to the elimination of expansion devices. This study investigates the flexural performance of ECC connection plates (ECP) for seamless RC bridge decks using finite element analysis. A three-dimensional ABAQUS model was developed and validated against available experimental results from the literature. Parametric analyses were performed to evaluate the effects of ECC thickness, reinforcement ratio, concrete strength, and ECC strength. The results show that ECP significantly improves flexural capacity and ductility compared with conventional RC connection plates. Under the same reinforcement ratio, the ultimate load and ductility coefficient increased by 35.1% and 31.3%, respectively. Increasing ECC thickness and ECC strength enhances both load-bearing capacity and deformation ability, while a higher reinforcement ratio increases ultimate load but reduces tensile strain capacity. A theoretical formula for predicting the flexural bearing capacity of ECP was derived and verified using numerical results. The findings provide a basis for the design and optimization of ECP in seamless bridge decks.